When fatigue postpartum is also prodromal - Alexandra Balshi; Riley Bove (Women's Health)
Postpartum fatigue (PPF) is a common issue affecting mothers, characterized by reduced capacity for physical and mental activity in the weeks to months following delivery. While often attributed to the demands of infant care, severe or atypical PPF can signal an underlying medical condition, such as multiple sclerosis (MS). In this narrative review, guidance is provided to clinicians on recognizing signs of severe or atypical PPF, differentiating it from MS-associated fatigue. Patients’ qualitative descriptions of fatigue, its intensity, and specific triggers can be particularly informative, as MS fatigue is severe, recurrent, often refractory to rest, and/or exacerbated by high temperatures. By identifying such cases early, healthcare providers can support timely diagnosis and intervention, ultimately improving outcomes for women who may be at risk for MS.